Opioid Risk Assessment in the Management of Low Back Pain - Weaver, Mandy (My University, 2017)
Problem: Currently, there is no assessment tool routinely in use to screen patients who are potentially at risk of abuse when prescribed opioids for pain. Risk management strategies should be used by primary care providers to minimize the risks associated with opioid use such as risk assessment, risk stratification, and monitoring for aberrant drug-taking behaviors. Methodology: This was a descriptive design project that targeted patients being seen for low back pain. The purpose of this project was to assess which patients who were seen for low back pain were at a greater risk of aberrant drug-related behaviors. The Opioid Risk Tool (ORT) was used in this project to measure the risk factors associated with drug abuse. Results: The final sample size was twelve. In the eight week period that the project was implemented seven men and five women presented with back pain and completed the ORT. Eight of the individuals included in the sample were found to be at low risk, two were moderate risk, and two were high risk for potential opioid abuse. Conclusion: Through consistent use of this tool providers can ensure that additional safeguards are in place to reduce the potential of opioid abuse. Although many clinics have adopted the use of screening tools for a variety of conditions, one for opioid abuse is not used consistently. Through the implementation of this project the aim was met which was to introduce the ORT to practice and determine the efficacy and feasibility for use in a primary care setting and to alert providers to patients who are at risk for potential opioid abuse therefore prompting them to explore alternative options for treatment.